Hydrothermal Synthesis, Crystal Structure, and Luminescent Property of a New Cd(II) Coordination Polymer With Three-Fold Interpenetrated pcu Topology. Issue 9 (1st September 2016) - Feng, Xiuling; Chen, Wanping; Xiang, Bolin
Abstract : A new three-dimensional (3D) coordination polymer, [Cd(pda)(bib)0.5 ]n (1 ), [H2 pda=1, 4-phenylenediacetic acid and bib=1, 4-bis(2-methyl-imidazol-1-yl) butane] was prepared by hydrothermal syntheses and characterized by single-crystal X-ray diffraction, FT-IR spectroscopy, and elemental analysis. Crystal structure determination revealed that complex1 features a threefold interpenetrated pcu framework. Furthermore, the luminescent property for complex1 is also investigated in solid state at room temperature.